PPK on JavaScript - Koch, Peter-Paul (Voices that matter, 2006)
Whether you're an old-school scripter who needs to modernize your JavaScripting skills or a standards-aware Web developer who needs best practices and code examples, you'll welcome this guide from a JavaScript master. Other JavaScript books use example scripts that have little bearing on real-world Web development and are useful only in the chapter at hand. In contrast, Peter-Paul Koch's book uses eight real-world scripts he created for real-world clients in order to earn real-world money. That means the scripts are guaranteed to do something useful (and sellable!) that enhances the usability of the page they're used on. The book's example scripts include one that sorts a data table according to the user's search queries, a form validation script, a script that shows form fields only when the user needs them, a drop-down menu, and a data retrieval script that uses simple Ajax and shows the data in an animation. After an overview of JavaScript's purpose, Peter-Paul provides theoretical chapters on the context (jobs for JavaScript, CSS vs. JavaScript), the browsers (debugging, the arcana of the browser string), and script preparation. Then follow practical chapters on Core, BOM, Events, DOM, CSS Modification, and Data Retrieval, all of which are explained through a combination of theoretical instruction and the taking apart of the relevant sections of the example scripts.